2021
DOI: 10.1111/ppl.13318
|View full text |Cite
|
Sign up to set email alerts
|

The cross‐kingdom roles of mineral nutrient transporters in plant‐microbe relations

Abstract: The regulation of plant physiology by plant mineral nutrient transporter (MNT) is well understood. Recently, the extensive characterization of beneficial and pathogenic plant‐microbe interactions has defined the roles for MNTs in such relationships. In this review, we summarize the roles of diverse nutrient transporters in the symbiotic or pathogenic relationships between plants and microorganisms. In doing so, we highlight how MNTs of plants and microbes can act in a coordinated manner. In symbiotic relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“… Ohkama-Ohtsu and Wasaki (2010) indicated that the symbiosis between plants and AM fungi might involve the same signaling pathway of the symbiosis between plants and rhizobia. Pathogens can regulate mineral nutrient transporter, which is also regulated by AM fungi, thereby influencing pathogen proliferation, biochemical defense of host, and related signal transduction mechanisms ( Sun et al, 2021 ). Therefore, indigenous microorganisms in the soil are recognized as the third party involved in AM fungi regulation for the host plant, not just soil-borne “free riders” ( Jansa et al, 2013 ); the cooperation and competition between AM fungi and indigenous microorganisms are inevitable in natural soil.…”
Section: Introductionmentioning
confidence: 99%
“… Ohkama-Ohtsu and Wasaki (2010) indicated that the symbiosis between plants and AM fungi might involve the same signaling pathway of the symbiosis between plants and rhizobia. Pathogens can regulate mineral nutrient transporter, which is also regulated by AM fungi, thereby influencing pathogen proliferation, biochemical defense of host, and related signal transduction mechanisms ( Sun et al, 2021 ). Therefore, indigenous microorganisms in the soil are recognized as the third party involved in AM fungi regulation for the host plant, not just soil-borne “free riders” ( Jansa et al, 2013 ); the cooperation and competition between AM fungi and indigenous microorganisms are inevitable in natural soil.…”
Section: Introductionmentioning
confidence: 99%
“…This response to low N seems to involve AMT2;3, and the simultaneous mutation of this AMT and PT restores the inhibition of AM fungi colonization. This indicates that AMT-mediated N transfer to the symbiotic interface also serves as a signal to regulate mycorrhizal colonization, in some cases going beyond the function of PT [ 141 , 161 , 162 ].…”
Section: Regulation Of Nutrient Exchange By P and N In Am Symbiosismentioning
confidence: 99%
“…The genes encoding function such as nutrient and mineral acquisition were more abundant for the communities on the lotus microhabitats. The role of microorganisms in maintaining the ow of nutrients to the host plant is crucial for overall plant growth and productivity, as the direct uptake of nutrients by plants via roots can lead to a nutrient depletion zone (Sun et al 2021).…”
Section: Differentially Abundant Potential Function Of Prokaryotic Co...mentioning
confidence: 99%